“Holding the Dream”: Women’s Favorite Reading Matter in a Portuguese Prison - Sequeiros, Paula (Qualitative Sociology Review, 2018)
The reading practices of women, mediated by a prison library in Portugal, constituted an interesting case study. In Santa Cruz do Bispo prison, female prisoners were increasingly aged and excluded from social groups, less literate, and educated. Many were first-time library users and some were beginning readers. This research aimed to understand their reading practices and preferences, their self-assigned meanings, and the roles of reading in prison. Having become aware that industrial literature romance novels were the most requested items, a critical comparative analysis of the three most requested titles was contrasted with readers’ favorite passages to foster a deeper understanding of their preferences and sustain an integrated analysis. Furthermore, a consensualized definition of a “good read” is presented. The results from ethnography and interviews to readers and staff are analyzed taking into account class, gender, ethnicity, age, occupation, and education of the detainees. Conclusions address the fact that although the prison’s educational service and imprisonment conditions propitiated an increase in reading generally, the library was oriented by educational targets and irresponsive to certain demands expressed by readers. Secondly, women readers were using the available top-selling romance novels to sustain their introspective and prospective work, while reckoning with their past and planning for their future. In addition to this reflexive stance, escapist entertainment and knowledge building were important reading purposes.